2013
DOI: 10.1371/journal.pone.0065661
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-Response Element Regulated Cell Cycle Arrests in Cancer Cells

Abstract: Recently, we have demonstrated that trichosanthin (TCS), a promising agent for the treatment of cervical adenocarcinoma, inhibited HeLa cell proliferation through the PKC/MAPK/CREB signal pathway. Furthermore, TCS down-regulated Bcl-2 expression was abrogated by a decoy oligonucleotide (OGN) to the cyclic AMP-responsive element (CRE). The decoy OGN blocked the binding of CRE-binding protein (CREB) to Bcl-2. These results suggested that CRE-mediated gene expression may play a pivotal role in HeLa cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Overall, selenite decreases the Bcl-2 expression by inhibiting the transcriptional activity of CREB in CRC cells. It has been reported that CREB regulates Bcl-2 expression in other cancer cells, such as non-small cell lung cancer (NSCLC) cell lines, MCF7 breast cancer cells and HeLa cell lines, which is consistent with our conclusion [8,13,34].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, selenite decreases the Bcl-2 expression by inhibiting the transcriptional activity of CREB in CRC cells. It has been reported that CREB regulates Bcl-2 expression in other cancer cells, such as non-small cell lung cancer (NSCLC) cell lines, MCF7 breast cancer cells and HeLa cell lines, which is consistent with our conclusion [8,13,34].…”
Section: Discussionsupporting
confidence: 93%
“…In the nucleus, activated CREB can bind to promoters containing a consensus sequence to enhance the transcription of various survival proteins including Bcl-2 [8,16,18,22]. Bcl-2 family proteins are essential regulators of selenite-induced apoptosis [23][24][25].…”
Section: Selenite Suppresses Creb Phosphorylation and Subsequently Rementioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have revealed that CREB phosphorylation is necessary for cell survival [7], promoting tumorigenesis in NSCLC, breast cancer [8,9], acute myeloid leukemia [10,11], hepatocellular carcinoma [12,13], glioma or for gliomagenesis [14,15] and tumor metastasis of melanoma cells [16,17]. Taken together with our previous reports that a cyclic-AMP-responsive element (CRE, TGACGTCA) decoy oligonucleotide blocked the CREB binding site on Bcl-2 [18,19] and cyclins [20] can abrogate antitumor drug-induced apoptosis and cell proliferation, it was suggested that CREB plays a key role in tumor progression. Nonetheless, the possible role of constitutively active CREB at Ser 133 (phosphorylated CREB [pCREB]) in the growth and metastasis of RCC has been little investigated.…”
supporting
confidence: 74%
“…Cyclic adenosine monophosphate (cAMP) response element-binding protein (CREB) is necessary for cell proliferation and apoptosis (Wang et al, 2013) because it regulates the expression of a repertoire of genes associated with cell survival. Those genes include B-cell lymphoma 2 (BCL2), B-cell lymphoma-extra large (BCLXL), and CFOS (Ferron et al, 2011;Han et al, 2013), and are particularly relevant during hypoxia (Meng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%